Metodología para el uso didáctico de las tecnologías de la información y la comunicación (TIC) - Zapata Jaramillo, Cinthya Julissa (2021)
ICT in the teaching-learning process confirmed their existence and permanence as tools for the educational process, causing great changes and transformations in teachers at different levels of training. The main objective of this research project is to implement a didactic methodology for the use of ICT that allows improving educational quality according to the needs and interests of students. This research will be carried out at the “Río Amazonas” Educational Unit of the Aguas Frías campus of the Mocache canton, during the first period 2021-2022. The design will be with a quali-quantitative approach through exploratory, descriptive research, with observation techniques and how The online survey instrument is divided into informative data, development of abilities, skills and values. The population under study will be for convenience. The results of the application of didactic methodologies will allow the teacher to obtain significant results with dynamic, innovative, critical, reflective learning. The permanence of students will be increased with prepared, creative, innovative teachers that enhance the quality of education at the unified general baccalaureate level. KEYWORDS: ICT; teaching-learning; methodology; didactic